Progress of LPS-induced apical lesion in rat immature mandibular molars. Issue 1 (April 2023) - Nakajima, Chikako; Fujita-Otani, Maiko; Mikuni-Takagaki, Yuko; Nakamura, Kuniomi; Hidaka, Kouki; Kawata, Akira; Kawamata, Ryota; Kimoto, Shigenari
Abstract: Introduction: The objective was to assess the process of apical periodontitis induced by injecting Porphyromonas gingivalis lipopolysaccharide (Pg LPS) that is followed by regeneration of roots in premature permanent tooth. A novel operation table was introduced to facilitate endodontic treatment of mandibular molars. Materials and Methods: Pulp of mandibular first molars of 6-week Wistar rats were exposed by drilling, inoculated with 0.6 μg Pg LPS and sealed with glass ionomer cement. After 1 and 2 weeks rats were sacrificed and the molar roots compared with those of vehicle controls by protein array analysis and (histo) morphology/chemistry. Micro-CT imaging visualized the lesion, and non-decalcified frozen serial sections were HE stained and subjected to TRACP-5b/ALP activity staining and immunohistochemical staining. Results: Quantitative induction of inflammation enabled us to examine the effects of LPS-injection: micro-CT images exhibited much larger radiolucent apical lesions than did controls; CD68 (M1+ M2±) cell surface marker was more intense in Pg-1w and then subsided while CD163 (M1- M2+) was more intense in Pg-2w. Staining of IL-4, which induces M2 polarization, and angiogenic markers, VEGF/CD34 was intense in Pg-1w than in controls. Conclusion: The introduced apparatus facilitated accurate mandible operation with ease. Thus, stages of pulpal infection were reproduced quantitatively with a small amount of Pg LPS. Proteins expressed in the root apex where inflammation occurred and the lesion in the surrounding alveolar bone revealed the inflammation time course in the immature permanent teeth. This mandibular model turned out quite useful for clinical and pharmaceutical developments in the future.